The effect of utilizing silica fume and eggshell ash on the geotechnical properties of soft kaolin clay - Zaini, M. S. I.; Muzamir, Hasan; Ling, Sin Yie; Khairil Azman, Masri; Putra Jaya, Ramadhansyah; Hyodo, Masayuki; Winter, Michael James (Penerbit Universiti Teknologi Malaysia, 2022)
The application of chemical stabilizer in soil stabilization can effectively reduce the negative environmental impact in the construction industry. However, the stabilization of soft clay remains a challenge due to the costly and non-eco-friendly materials such as cement and lime. This research demonstrates the combination of SF and ESA in stabilizing the kaolin soils, based on the basic engineering properties and undrained shear strength (USS). Its effect was studied via the inclusion as cement replacement material in kaolin soil at 2, 4 and 6% (by weight of dry soft kaolin clay soil) of SF and ESA substitutions of 3, 6 and 9% (by weight of dry soft kaolin clay and SF content). The result shows a considerably lower specific gravity (4.9% reduction), reduced plasticity index (PI)(48.4% reduction), decreased maximum dry density (MDD) (5.5% reduction), increased optimum moisture content (OMC)(8.7% increment), and higher USS (68.8%). In conclusion, the combinations of SF and ESA as soil stabilization agents successfully enhance the soil strength of the kaolin opening a route to the low cost and eco-friendly materials in soil stabilization.